Cross-cultural differences in children' motor competence are accumulating along the age and in the interaction of body weight status - Lopes, Vitor P. (2018)
The present study examined differences in 5–9-year-old children’s motor competence (MC) across Northern-, Central-, and Southern European countries using the Körperkoordinationstest für Kinder (KTK). A secondary aim was to examine whether the cross-cultural differences in MC accumulate in the interaction with children’s age group and body weight status determined as being normal or overweight. Methods: Data was pooled from four independent studies conducted in Finland (mean age 7.31 +/− 1.38 years, n = 360 + 432), Belgium (mean age 8.19 +/− 1.14 years, n = 1936) and Portugal (mean age 8.31 ± 1.02 years, n = 758) between years 2008 and 2016. Differences between countries in the raw scores of KTK and the interaction effects were tested by using oneand two-way analyses of covariance. Age, sex and BMI percentile were used as covariates. Results: Country explained significantly (9%) the variance in MC, meanwhile age (44%) and BMI percentile (5%) were significant covariates. Age and country had significant interaction effect (6%), as well as country and body weight status (2%). Conclusions: Results strengthen existing literature showing cross-cultural differences in children’s MC. Based on the present results, the differences are accumulating along the childhood. Novel finding of the study suggests polarization in the development of MC between normal and overweight children is differing across countries. Further studies is needed for exploring the reasons explaining the age and body weight status interaction effects in cross-cultural differences in children’s MC